Quiet : the power of introverts in a world that can't stop talking - Cain, Susan (Crown Pub., 2012)
At least one-third of the people we know are introverts. They are the ones who prefer listening to speaking, reading to partying; who invent and create but prefer not to pitch their own ideas; who favor working on their own over brainstorming in teams. Although they are often labeled "quiet," it is to introverts we owe many of the great contributions to society--from Van Gogh's sunflowers to the invention of the personal computer. Passionately argued, impressively researched, and filled with the indelible stories of real people, Quiet shows how dramatically we undervalue introverts, and how much we lose in doing so.